Pengaruh Fungsi Pelayanan Administrasi Dan Kinerja Pegawai Terhadap Peningkatan Mutu Pelayanan Publik Di Kecamatan Banjarbaru Kota - witanti, sri (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2024)
The lack of maximum service functions provided by officials to the community has an impact on the community's lack of satisfaction with service providers. The aim of this research is to determine the influence of administrative service functions and apparatus performance on improving public services. A qualitative descriptive approach. The sample was determined as 30 people using incidental sampling technique, a data collection technique through inquiry and direct observation supported by the documentation found. Data analysis uses a percentage tabulation system to determine the level of achievement of each question item. The results of the research show that the function of administrative services and performance in Banjarbaru Kota District is less than optimal due to the low competence of officials in their work. Then, internal supervision lacks communication regarding operational activities, with a lack of disciplinary communication from the officers concerned.